2008
DOI: 10.1016/j.heares.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Responses of cochlear nucleus neurons to harmonic and mistuned complex tones

Abstract: Preliminary measurements of the representation in the cochlear nucleus (CN) of harmonic tones, harmonic tones with mistuned components, and double harmonic tones are reported. These data indicate that, unlike auditory nerve fibers and IC neurons, neurons in the CN may exhibit one of several qualitatively-different response patterns when stimulated with mistuned tones. Primarylike neurons synchronized their discharges to 2-3 individual stimulus components, much like auditory nerve fibers do. Chopper neurons ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…In the current study, it is likely that the effects of age on the cochlea were similar in older musicians and nonmusicians, as there were no differences in their pure-tone thresholds. Although we did not investigate subcortical responses, it is likely that the ORN is related to processing of the mistuned harmonic in subcortical structures (Sinex, 2008;Sinex, Guzik, Li, & Sabes, 2003;Sinex, Sabes, & Li, 2002). Thus, although the ORN is generated along the superior temporal plane, ORN generation likely depends on earlier processing of the mistuned harmonic in subcortical structures.…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, it is likely that the effects of age on the cochlea were similar in older musicians and nonmusicians, as there were no differences in their pure-tone thresholds. Although we did not investigate subcortical responses, it is likely that the ORN is related to processing of the mistuned harmonic in subcortical structures (Sinex, 2008;Sinex, Guzik, Li, & Sabes, 2003;Sinex, Sabes, & Li, 2002). Thus, although the ORN is generated along the superior temporal plane, ORN generation likely depends on earlier processing of the mistuned harmonic in subcortical structures.…”
Section: Discussionmentioning
confidence: 95%
“…Sinex and coworkers (Sinex, 2008; Sinex and Li, 2007) measured responses to concurrent harmonic complexes in the IC and cochlear nucleus (CN) of anesthetized chinchillas. In the IC, the responses to double harmonic complexes showed little or no synchrony to individual harmonics, and usually followed envelope fluctuations resulting from beats between adjacent components (Sinex and Li, 2007).…”
Section: Neural Basis Of the Perception Of Concurrent Harmonic Soundsmentioning
confidence: 99%
“…In contrast, Chopper neurons exhibited little synchrony to individual components, and tended to follow envelope fluctuations resulting from interactions between adjacent components (Sinex, 2008). Based on these results and earlier ones, which showed that ANFs typically synchronized to individual components in harmonic complex tones or complex tones containing a mistuned component (Sinex et al, 2003), Sinex (2005, 2008) suggested that neural responses to complex tones undergo a major transformation at the level of the lower brainstem, which results in qualitatively different responses to harmonic and inharmonic stimuli below and above the CN. Below the CN, neurons usually synchronize to individual components in a complex tone, regardless of whether these components are harmonically related or not.…”
Section: Neural Basis Of the Perception Of Concurrent Harmonic Soundsmentioning
confidence: 99%
“…Only a few studies have directly examined the representation of the F0s of concurrent complex tones in the AN and CN (Palmer 1990, 1992; Tramo et al 2000; Keilson et al 1997; Sinex 2008). Using two concurrent vowels with F0s of 100 and 125 Hz, Palmer found that the temporal discharge patterns of AN fibers contained sufficient information to identify both F0s.…”
Section: Introductionmentioning
confidence: 99%